Dragonfly in amber [compact disc, unabridged] - Gabaldon, Diana (Gabaldon, Diana. Outlander novels., 2013)
For twenty years Claire Randall has kept her secrets. But now she is returning with her grown daughter to Scotland's majestic mist-shrouded hills. Here Claire plans to reveal a truth as stunning as the events that gave it birth: about the mystery of an ancient circle of standing stones ... about a love that transcends the boundaries of time ... and about James Fraser, a Scottish warrior whose gallan try once drew a young Claire from the security of her century to the dangers of his ... Now a legacy of blood and desire will test her beautiful copper-haired daughter, Brianna, as Claire's spellbinding journey of self-discovery continues in the intrigue-ridden Paris court of Charles Stuart ... in a race to thwart a doomed Highlands uprising ... and in a desperate fight to save both the child and the man she loves ...